PENGARUH MEDIA POSTER BERKALENDER TENTANG PEMERIKSAAN IVA TERHADAP PERILAKU MELAKUKAN IVA PADA WANITA USIA SUBUR - Eka Nofrida Fauzi; Sri Utami; Ganis Indriati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Visual Inspection Acetic (VIA) is one of the practical early detection efforts for cervical cancer, it is very easy to do with simple equipment and the price is affordable for the wider community. This study aims to determine the effect of health education with calendar poster media about VIA examination on the behavior of performing VIA in women of childbearing age for cervical cancer prevention. This study used a pre-experimental design with one group pre-test post-test design. This research was conducted in the Puskesmas Sapta Taruna, Bukit Raya with a sample of 34 respondents who were taken based on inclusion criteria using purposive sampling. Data collection tool using a questionnaire. Analysis of the data used the Wilcoxon. The results of the univariate analysis of the majority of respondents were in the age of 30-40 years (52,9%). The majority of respondents are at the education level of SMA (58,8%). The majority of occupations are domestic workers (79,4%). The results of bivariate analysis with wilcoxon obtained p value (0.000) < α (0.05). This means that Ho is rejected, it can be concluded that there are differences in the behavior of women of childbearing age before and after being given health education with calendar poster. Health education with calendar poster media about VIA examination has an effect on the behavior of performing VIA in women of childbearing age for cervical cancer prevention. The results of this study are expected to be used as a reference for health facilities in providing information and services regarding VIA examinations to improve behavior in conducting VIA as an early detection of cervical cancer.Keywords: calendar poster; cervical cancer; VIA examination; VIA screening.